Effects of sensory room intervention on autonomic function in healthy adults: A pilot randomized controlled trial - Hikari Otsuka; Keisuke Irie; Tomohiro Kogata; Azumi Onitsuka; Hiroyuki Inadomi (PLoS ONE, 2025)
Sensory rooms are those equipped with various visual, auditory, and other sensory items that can be adjusted according to user preferences. Although several studies have reported the effectiveness of sensory rooms, their physiological effects remain unclear. This pilot study aims to investigate the effect of sensory rooms on vagal function, mood states, and attentional functions. Thirty-nine healthy young adults were randomly divided into the sensory room intervention (SRI) and sedentary activity (SA) groups, and given a 30-minute intervention. The SRI group spent time in a dimly lit room with beaded cushions and aroma oils. The SA group engaged in activities such as handicrafts and puzzles. We compared changes in respiratory sinus arrhythmia (RSA) at rest, RSA variability during discomfort sensory stimulation, mood states, and attentional functions between the groups, both before and after the intervention. As a result, 1) SRI significantly increased RSA compared with SA. 2) It also reduced the variability of RSA in response to specific sensory stimuli compared with SA. 3) However, no significant differences existed in negative mood or attentional function between the groups. The results suggest that sensory rooms might contribute to the sensory modulation, including that of the autonomic nervous system. Further investigation with larger samples in clinical settings, particularly among individuals with sensory modulation issues and mental illness, is necessary to confirm and generalize these findings.